Syarah Hadis Perihal Seni Gambar dan Memahat Patung - Muhamad Zarkasih Nur; Susanti Vera (Gunung Djati Conference Series, 2022)
The purpose of this study was to examine the understanding of hadith about the art of drawing and sculpture. This research method uses a qualitative type through literature study with an analytical approach of matan and syarah hadith. The results and this discussion conclude that the artwork is an image that can be observed by the eye and can be felt by the touch. The terms that represent the art of drawing are the words tashwir, tamatsil, and rasm. Deep drawing activities are permitted on the conditions that they paint inanimate objects, then there are two forms of conclusions regarding drawing. First, it is forbidden to sculpt or draw living creatures that are alive with the aim of emulating Allah's creation and praising it, secondly, it is permissible to draw or sculpt animate but not worshiped creatures.